Synapsin I Controls Synaptic Maturation of Long-Range Projections in the Lateral Amygdala in a Targeted Selective Fashion - Lugarà, Eleonora; De Fusco, Antonio; Lignani, Gabriele; Benfenati, Fabio; Humeau, Yann (Frontiers in Cellular Neuroscience, 2019)
The amygdala, and more precisely its lateral nucleus, is thought to confer emotional valence to external stimuli by generating long-term plasticity changes at long-range projections to principal cells. Aversive experience has also been shown to modify pre- and post-synaptic markers in the amygdala, suggesting their possible role in the structural organization of adult amygdala networks. Here, we focused on the maturation of cortical and thalamic long-term projections on principal neurons and interneurons in the lateral amygdala (LA) and on how it is affected by deletion of the presynaptic protein synapsin I. We firstly performed dual electrophysiological recordings of identified cells in juvenile and adult GAD67-GFP mice after independent stimulation of cortical and thalamic afferent systems. The results demonstrate that synaptic strengthening occurs during development at synapses projecting to LA principal neurons, but not interneurons. As synaptic strengthening underlying fear conditioning depends on the presence and increasing expression of synapsin I, we successively tested if synapsin I contributes to synaptic strengthening during development. Interestingly, the physiological strengthening of cortical and thalamic synapses projecting to LA principal neurons was virtually abolished in synapsin I knockout mice, while no differences were observed in the excitatory projections to interneurons, suggesting that the synapse-specificity of synaptic strengthening by synapsin I is attributable to its neuronal target. Immunohistochemistry analysis demonstrated that the presence of synapsin I is restricted to excitatory contacts projecting to principal neurons in LA of adult mice. These results indicate that synapsin I is a key regulator of the maturation of synaptic connectivity in this brain region and that is expression is dependent on postsynaptic identity.